Cost Minimization Analysis of Analgesics for Tooth Extraction - Lubis, Yolanda Eliza Putri; Rizky, Muhammad Irvan; Ginting, Chrismis Novalinda; Manalu, Putranto (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2025)
Tooth extraction remains a common dental procedure in Indonesia owing to the increasing prevalence of oral health problems. Despite standard operating procedures and analgesics, pain management following tooth extraction remains a challenge. By analyzing different analgesic options and their associated costs, this study seeks to provide valuable insights for healthcare providers and patients in selecting the most effective and affordable pain management strategies. This study aimed to assess the cost-effectiveness of analgesic drugs for pain management after tooth extraction. This cross-sectional study was conducted on 92 patients who underwent dental extractions in Pabatu Hospital, Serdang Bedagai. Secondary data from the medical records were analyzed to assess patient demographics, diagnoses, analgesics used, pain levels, and treatment costs. Cost minimization analysis (CMA) was employed to compare the direct medical costs associated with different analgesics. The analysis highlighted that the combination of paracetamol and Na-diclofenac had the lowest average cost per patient (IDR 238,150.00), making it a financially viable option for both healthcare providers and patients. In contrast, the average cost of ibuprofen was significantly higher (IDR 433,954.97), suggesting that it may not be the best choice when considering both effectiveness and expense. Approximately 80% of the total direct medical costs for all three analgesics are attributed to procedure and treatment expenses, indicating that the choice of analgesics has a relatively small impact on overall costs. These findings advocate the use of cost-effective analgesic combinations in clinical practice, particularly in settings in which budget constraints are a concern.